THE SELF-DIFFUSION OF SILICON AND OXYGEN IN DIOPSIDE (CAMGSI2O6) LIQUID UP TO 15 GPA - Reid J.E.; Poe B.T.; Rubie D.C.; Zotov N.; Wiedenbeck M. (My University, 2001)
The self-diffusivities of silicon and oxygen in diopside (CaMgSi2O6) liquid have been measured at pressures and temperatures up to 15 GPa and 2300°C, using a 1200-tonne multianvil apparatus. Diffusion couples were prepared using finely ground, diopside glass, half of which was enriched in tracer isotopes 18O (5%) and 30Si (12%). Results indicate that silicon and oxygen self-diffusivities are coincident (within an accuracy range of 10% RSD, 1σ) up to 13 GPa and show an initial decrease with pressure up to 11 GPa (oxygen self-diffusivities are 9.8x10-10 m2/s at 3 GPa and 3.9x10-10 m2/s at 11 GPa) after which there is an increase with pressure up to 15 GPa (9.1x10-10 m2/s) at 2000°C. The activation energy of self-diffusion of both silicon and oxygen was calculated to be 267 kJ mol-1, with no observable pressure effect up to 3 GPa. Self-diffusivity is inversely proportional to viscosity, the relationship between these properties being well approximated by the Eyring equation using the diameter of an oxygen anion as the translation distance. The calculated viscosities are in good agreement with previous direct viscosity measurements at lower pressure although the previously found high positive activation volumes were not reproduced.
Keywords: SELF-DIFFUSION; DIOPSIDE MELT; HIGH PRESSURE; VISCOSITY